Risk factors related to malaria incidence at Santu’un village, Tabalong District, South Kalimantan Province - Junus Widjaja Supargiyono Tri Baskoro Tunggul Satoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Santu’un Village is one of malaria endemic areas in Muara Uya Sub district, Tabalong District, South KalimantanProvince, Indonesia. Annual Parasite Incidences (APIs) from 2007 to 2009 were 11.4, 82.9, and 25.8‰ respectively.The majority of Muara Uya population are rubber tappers, gold miners and loggers in the forest. Moreover, most ofthe Muara Uya population do not use mosquito nets when sleeping at night. These occupations and communityhabits may contribute in high malaria incidence in Muara Uya. However, study concerning risk factor of malaria hasnot been performed yet. The study was conducted in order to evaluate risk factors that might correlate with malariaincidence in Santu’un village, Muara Uya subdistrict. Two hundred and ninety one subjects were enrolled in thisstudy. Those consisted of 70 people whom microscopically malaria positive and 221 people whom malaria negative.Household visits were conducted to each subject to perform interviews. Data collection of malaria risk factors wasobtained using questionaire. The results indicated that three main occupations, loggers, gold miners and rubbertapper, were significantly represent risk factors of malaria incidence. The community habits that also significantlycorrelated with malaria incidence were the not using of mosquito repellents and not using bed nets. Two clusteringcases were also observed during the year of 2010. The coordinate of the first cluster was 1.863500 S and 115.606700E with diameter of 0.65 km and the coordinate of the second cluster was 1.838667 S and 115.607200 E withdiameter of 0.67 km. In conclusion, in Santu’un village, the risk factor that correlated with the malaria incidencewere loggers, gold miners, rubber tappers. In addition the not using of mosquito repellents and not using bed netswere also risk factors of malaria incidence.Key words: malaria -risk factors-annual parasite incidence-Muara Uya-South Kalimantan